The daughter's tale : a novel - Correa, Armando Lucas, 1959-; Caistor, Nick (New York : Washington Square Press/Atria Books, 2020)
"BERLIN, 1939. The dreams that Amanda Sternberg and her husband, Julius, had for their daughters are shattered when the Nazis descend on Berlin, burning down their beloved family bookshop and sending Julius to a concentration camp. Desperate to save her children, Amanda flees toward the south of France, where the widow of an old friend of her husband's has agreed to take her in. Along the way, a refugee ship headed for Cuba offers another chance at escape and there, at the dock, Amanda is forced to make an impossible choice that will haunt her for the rest of her life. Once in Haute-Vienne, her brief respite is interrupted by the arrival of Nazi forces, and Amanda finds herself in a labor camp where she must once again make a heroic sacrifice. NEW YORK, 2015. Eighty-year-old Elise Duval receives a call from a woman bearing messages from a time and country that she forced herself to forget. A French Catholic who arrived in New York after World War II, Elise is shocked to discover that the letters were from her mother, written in German during the war. Despite Elise's best efforts to stave off her past, seven decades of secrets begin to unravel. Based on true events, The Daughter's Tale chronicles one of the most harrowing atrocities perpetrated by the Nazis during the war. Heartbreaking and immersive, it is a beautifully crafted family saga of love, survival, and redemption,"--Amazon.
Translated from the Spanish.
Translation of: La hija olvidada.
Originally published: Spain : Atria Estanol, 2019.
Includes a Reader's Guide and questions for discussion.
Keywords: Holocaust, Jewish (1939-1945) -- Germany -- Fiction; Jewish families -- Germany -- Fiction; Jews, German -- France -- Fiction; World War, 1939-1945 -- Underground movements -- France -- Fiction; World War, 1939-1945 -- Atrocities -- France -- Fiction; Mothers and daughters -- Fiction; Survival -- Fiction; Reminiscing in old age -- Fiction; Holocaust survivors -- United States -- Fiction; Oradour-sur-Glane Massacre, Oradour-sur-Glane, France, 1944 -- Fiction; Historical fiction